The impact of perioperative acute kidney injury/failure on short and long surgical outcomes - Mok, Valerie; Nixon, Jonathan; Hu, Jie; Ma, Daqing (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
The development of acute kidney injury after surgery is associated with significant mortality and morbidity and with worse short and long-term outcomes. Patients who develop acute kidney injury are at an increased risk of developing long-term renal dysfunction, which leads to lower quality of life and greater financial burden on the healthcare system. Although there are various systems to classify the severity of acute kidney injury, most systems only measure components that deteriorate after significant renal damage, such as urine output and serum creatinine. Surgical trauma and stress trigger acute kidney injury development, in addition to multiple co-morbidities, cardiovascular disease, and postoperative factors. The pathophysiology of acute kidney injury is complex, and this is reflected in the heterogenous population that is affected. Treatment is largely supportive and focuses on ensuring adequate renal perfusion, correcting electrolyte abnormalities and avoiding further renal injury. Current research focuses on novel biomarkers that detect decreased renal function earlier and that the deteriorating renal function can be treated before long-lasting damage occurs. This review discusses the epidemiology, aetiology, risk factors, and short and long-term surgical outcomes of acute kidney injury. Treatment, prevention, and recent developments in future research are also discussed. Graphical Abstract